Unexpected loc.sg. -â in High Latvian - Kalniņš, Aigars (Baltistica, 2024)
This paper investigates ā-stem locative singular endings in the High Latvian dialects. It is shown that the phenomenon of labialization of inherited *ā largely rebuts the traditional comparison of Low Latvian loc. sg. -â with High Latvian -â because in most dialects we in fact expect -ô, ‑ôa or ‑uô instead. Following an alternative line of thought, this “unexpected” loc. sg. -â is rather identified with loc. sg. -ai and a new sound law is proposed, according to which word-final, unaccented *-aî is widely monophthongized to -â. Apart from the locative singular the effects hereof are also seen in navâ (
Keywords: Latvian; High Latvian; comparative linguistics; dialectology; locative; inessive; adessive